Result of Counseling for Meniere's Disease - Onuki, Junichi; Iida, Masahiro; Odagiri, Kyoko; Wada, Ryoko; Takahashi, Masahiro (Equilibrium Research, 2004)
In our regular otolaryngology practice, we encounter patients with Meniere's disease exacerbated by stress. We counsel such patients on the behavioral and lifestyle changes they can make to improve their disease condition. We conducted a study investigating the effect of our counseling program on the hearing level of patients with Meniere's disease. The subjects were 37 Meniere's disease patients who underwent counseling and drug treatment and 29 Meniere's disease patients who underwent only drug treatment. The counseling focused on helping patients recognize their own behaviors that produce stress, helping patients learn to relax, helping patients incorporate sweat-producting exercise into their routines, and helping them remove sources of stress if possible. The content of the counseling differed slightly on a case-by-case basis. After 1 year, audiograms were obtained from all patients in each group, and these audiograms were compared with those obtained before the study began. The change after 1 year was then compared between groups. In the group that underwent counseling, audiograms improved in 29 patients (78.4%), did not change in 5 (13.5%), and worsened in 3 (8.1%). In the drug treatment group, audiograms improved in 16 patients (52.2%), did not change in 11 (37.9%), and worsened in 2 (6.9%). Thus, the counseling was shown to be effective in improving the hearing level of patients with Meniere's disease influenced by stress. Counseling has not been established as a treatment strategy for Meniere's disease, but at present, drug regimens and surgery are the only other options. According to our findings, we recommend counseling along with drug therapy in keeping with the patient's lifestyle to improve the hearing ability of those with Meniere's disease.